EKSISTENSI BARZANJI DI TENGAH MODERNISASI (Studi Kasus di Kelurahan Cabenge Kecamatan Lilirilau Kabupaten Soppeng) - Masriani Masriani; Wahyuni Wahyuni; St Syakirah Abunawas (SOSIORELIGIUS, 2021)
This study describes the existence of barzanji in the midst of modernization in Cabenge Village, Lilirilau District, Soppeng Regency. This study uses a qualitative descriptive research using a sociological and phenomenological approach. The theory used in this research is Kirkegaard's theory of existence. According to Kirkegaard, existence is a brave decision taken by humans to determine their lives, and accept the consequences that humans have taken. The results of this study indicate that (1) the existence of barzanji in the midst of modernization among parents has not experienced any change or fading of tradition, whether it is the way of implementation. The knowledge of the Cabenge community about barzanji continues to this day (2) the impact of modernization on the existence of barzanji, in the Cabenge community among young people, it seems that they want to eliminate the barzanji tradition because they have chosen technology, rather than learning to pray.